Is alteration of warfarin regimen necessary before dental extractions in Taiwanese patients? Results of a retrospective cohort study - Shin-Yu Lu; Chi-Yu Tsai; Sheng-Nan Lu; Liang-Ho Lin (Elsevier, 2015)
Background/purpose: Most Western studies do not recommend interrupting warfarin therapy or replacing it with heparin prior to tooth extraction if the international normalized ratio (INR) levels are maintained. However, this issue remains controversial in Taiwan. The aim of this study was to investigate whether Taiwanese patients who had an INR within the therapeutic range required cessation of warfarin prior to dental extractions. Materials and methods: A total of 60 patients on warfarin with INR <4.0 who underwent 207 dental extractions in 70 occasions were divided into two groups. Thirty-two patients were allocated to the control group (warfarin stopped and switched to heparin under hospitalization) with average preoperative INR (range) from 2.30 (1.32-3.12) brought down to 1.14 (1.04-1.32), and 28 patients were allocated to the study group (warfarin continued) with an average preoperative INR of 1.95 (1.06-3.08). Results: The incidence of postoperative bleeding in the study group was higher (3/33, 9.1%) than in the control group (3/37, 8.1%), but this difference was not significant. Local hemostasis with Gelfoam sponge was sufficient in most patients. Postoperative hemorrhage can be successfully managed by repacking with Gelfoam impregnated with tranexamic acid powder in five patients and resuturing in one patient. Conclusion: The study proved that dental extractions can be performed without interruption or alteration of warfarin regimen in Taiwanese patients, provided the INR is below 4.0. A sufficient hemostasis can be obtained using local measures. This approach can save these individuals from becoming exposed to the risk of thromboembolism and the inconvenience of bridging anticoagulation with heparin.